Reconceptualising the Cyclical Process in Participatory Action Research: A Focus on the Individual-Collective Dynamics - Catrin Noone; Sui-Ting Kong (International Journal of Qualitative Methods)
This article proposes a new multi-helix model for Participatory Action Research (PAR) to capture the individual-collective dynamics in the cyclical process. By offering a critique of Lewin’s traditional action-reflection cycle, we outline the dangers of assuming synchronicity between the ‘individual’ and the ‘collective’ and the reflection-action linearity pervasive to existing PAR cycles. We draw on the authors’ experiences of carrying out PAR in various cultural, social and professional contexts to explore (mis)aligned rates and weights of participation, considering these alongside temporality and materiality within the PAR process. We argue that collective reflective practice is the site of both the performance and the construction of the collective, which benefit from embracing individuals’ changing concerns and life projects. Informed by the work of Archer (2000, 2007) and Schatzki (2009, 2017), the proposed model harnesses PAR’s potential for democratising knowledge production by exposing the social and emotional work carried out by participatory researchers, evoking timely implications for a practice turn in PAR.